Peningkatan Keterampilan Menulis 'Descriptive Text' dengan Menggunakan Media 'Magic Card' pada Mata Pelajaran Bahasa Inggris di Kelas X (Improving the Descriptive Text Writing Skill Using Magic Cards in English Class in 10th Grade) - Atiek Indriyastuti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2018)
The purpose of the research was to find out how far the improvements of tenth grade students’ skills were in writing descriptive text. The research was conducted in Class of X-7 at SMA Negeri 15 Semarang in the 2nd semester of the Academic Year 2014-2015 as a result of the use of magic card media. This research was also conducted to find out the students’ improvement levels of knowledge and learning attitudes during the learning period. Method used in the research was Class Action Research with technique of cycles, consisting of cycle I and II. Data collection tool used for quantitative data was in the form of written daily test and, the tools for qualitative data were observation, self-reflection, and peer-review sheets as well as performance appraisal rubrics. The research results showed that magic card media could improve the skills in writing descriptive text. The learning mastery improved from 28.13% to 50% in cycle I and 84.38% in cycle II. The students’ skill in writing descriptive text improved up to 5.31% compared to the average learning outcomes in the pre-cycle stage. And the learning outcomes in cycle 2 increased up to 6.40% from the average learning outcomes in cycle I.